Conversational Sales for OEM Apps - Felix Kuhnert; Stefan Pühl (Marketing Review St.Gallen, 2023)
Carmakers should leverage conversational sales to turn their apps into two-way sales and marketing channels. They can learn from retailers and social media whose apps are effective conversational sales tools that enhance customer loyalty.
Keywords: 650